Effectiveness of household-level interventions for reducing the impact of air pollution on health outcomes – a systematic review - Salve, Harshal Ramesh; Nawaz, Huma; Dey, Sagnik; Krishnan, Anand; Sharma, Preeti; Madan, Karan (Frontiers in Environmental Health, 2024)
Background and aim Several air pollution mitigation initiatives have been researched worldwide to see how efficient they are at reducing air pollution and the related health benefits. The effectiveness of these interventions for improving health outcomes is key for scaling up and increasing uptake of same by policymakers and people. We aimed to synthesize scientific evidence about the effectiveness of household-level interventions on air quality and health outcomes using a systematic approach. Methods Comprehensive strategy was used to carry out a literature search in PubMed, Cochrane, and Google scholar by two independent investigators using keywords and Medical Subject Heading terms. Research articles published till the year 2021 focusing on interventions for improvement in air quality and health were selected using pre-specified eligibility criteria. All abstracts for inclusion were reviewed independently by two reviewers. In case of doubt, the articles were included for full-text review. Disagreements were resolved by discussion with the third investigator. The quality of the studies and risk of bias was assessed using the Joanna Briggs Institute critical appraisal tool and Cochrane Risk of Bias tool, version 2.0. Effect estimates were reported using odds ratio, relative risks, difference in mean, and percentage changes with 95% confidence intervals. PRISMA guidelines were used to conduct and report the systematic review. The review was registered in PROSPERO (CRD42022295393). Results The search resulted in the identification of 46,809 studies and 18 of them were finally included in the review using eligibility criteria. The household-level interventions were categorized mainly into air purifiers/electric heater use, cookstove use, and behavioural change interventions. These interventions resulted in a decrease in the number of daytime asthma attacks by 33%, an increase in FEV1 by 4.4%, −1.4% and 0.8% overall percent change in microvascular and lung function. PM2.5 was the most commonly reported air pollutant, its concentrations reduced in the range between 31% and 53% across the studies. Conclusion Our review provided consistent evidence for the effectiveness of household-level interventions thus associated with improvements in cardiovascular and respiratory symptoms. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=295393, identifier, CRD42022295393